The sublime country: Sublime and spectral aesthetics in the poetry of Juan Gelman (Anclajes, 2026)
The logic of the sublime and the logic of the spectral form two highly productive aesthetic-political frameworks in Juan Gelman’s poetic work. Together, they shape a literary experience that conveys a sentiment deeply marked by revolutionary defeat and exile. In addition to a hermeneutic approach to Gelman’s poetry, the analysis explores the relationship between a sublime mode of experience—made possible through rhetorical strategies rooted in Romanticism—and a phenomenology of political experience that, following Jacques Derrida, positions spectrality as a form of presence emerging out of the ruins of history.
Keywords: Juan Gelman; Poetry; 20st Century; Argentina